2014
DOI: 10.1371/journal.pone.0105581
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Prevalence among Northern Mexican Adult Population

Abstract: Background and AimsDietary habits in the Mexican population have changed dramatically over the last few years, which are reflected in increased overweight and obesity prevalence. The aim was to examine the prevalence of metabolic syndrome (MetS) and associated risk factors in Northern Mexican adults aged ≥16 years.Methods and ResultsThe study was a population-based cross-sectional nutritional survey carried out in the State of Nuevo León, Mexico. The study included a sub-sample of 1,200 subjects aged 16 and ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
47
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 32 publications
8
47
2
1
Order By: Relevance
“…The development of metabolic syndrome is influenced by a combination of genetic and environmental factors. Among the environmental factors, long-term high-fat intake is most intensively studied because of its contribution to the development of metabolic syndrome in human beings and rodents (Salas et al, 2014). Results of this study are consistent with results of previous research works that have shown the antihypercholesterolemic effects of Z. officinale (Prasad et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The development of metabolic syndrome is influenced by a combination of genetic and environmental factors. Among the environmental factors, long-term high-fat intake is most intensively studied because of its contribution to the development of metabolic syndrome in human beings and rodents (Salas et al, 2014). Results of this study are consistent with results of previous research works that have shown the antihypercholesterolemic effects of Z. officinale (Prasad et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…In developed countries metabolic syndrome appears to affect around 25 % of the population (Salas et al, 2014). The modern lifestyle of increased intake of high-calorie food contributes to the rising prevalence of obesity and type 2 diabetes (Isordia- Salas et al, 2012;Salas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Own study confirmed that HTN is slightly more frequently diagnosed in women than in men; 23 however, many authors indicated that HTN is more common in men. [24][25][26][27][28] In Bosnia and Herzegovina and Brazil, approx. 40% of men are treated for HTN, which is the same result as the one obtained in own study.…”
Section: Discussionmentioning
confidence: 99%
“…The MetS and its individual components have been widely studied in adults (3)(4)(5), as well as in younger ages (6,7); however, association between AOb measured by waist circumference and elevated BP, has not been examined comprehensively in young university students of Mexico. Our group estimated a national wide prevalence of MetS of 15.8% in young people from Mexico (7).…”
Section: Introductionmentioning
confidence: 99%